EKSPLORASI ETNOMATEMATIKA OBJEK BANGUNAN MENARA KUDUS SEBAGAI SUMBER BELAJAR GEOMETRI - Nura Milla Husna; Zaenuri, Zaenuri; Walid, Walid; Mulyono, Mulyono; Munahefi, Detalia Noriza (Universitas Muhammadiyah Metro, 2024)
Several previous studies have stated that the ability of students in Indonesia is still relatively low in solving real mathematical problems, therefore learning mathematics needs to be related to the environment around students. This study aims to explore and analyze some mathematical concepts contained in the object of the Kudus Tower building in Kudus Regency. The research method used is an explorative-descriptive method with an ethnographic approach with the aim of exploring and analyzing some of the mathematical concepts contained in the ornaments or buildings of the Holy Tower. The data collection technique used an interactive model, namely data reduction, data presentation and conclusion making. Triangulation was also carried out by researchers to check the validity of the data. The results showed that on the object of the Kudus Tower building in Kudus Regency there are ethnomathematics concepts consisting of (a) Circle concept; (b) rhombus; (c) square; (d) rectangle; (e) equilateral triangle; (f) isosceles triangle; (g) trapezoid; (h) cube; (i) beam, (j) trapezoidal prism, and (k) quadrilateral pyramid. Some of these ethnomathematics concepts have relevance to mathematics learning at the primary and junior secondary education levels in geometry material.